2022
DOI: 10.1080/21681805.2022.2123039
|View full text |Cite
|
Sign up to set email alerts
|

Community-onset urosepsis: incidence and risk factors for 30-day mortality – a retrospective cohort study

Abstract: Background: Urosepsis is a life-threatening condition that needs to be addressed without delay. Two critical issues in its management are: (1) Appropriate empirical antibiotic therapy, considering the patients general condition, comorbidity, and the pathogen expected; and (2) Timing of imaging to identify obstruction requiring decompression. Objectives: To identify risk factors associated with 30-day mortality in patients with urosepsis. Methods: From a cohort of 1,605 community-onset bloodstream infections (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(34 reference statements)
0
7
1
Order By: Relevance
“…Known risk factors for 30-day mortality, such as age, comorbidity, dependency, HCA-urinary sepsis, septic shock and IEAT [ 31 , 32 , 33 , 34 , 35 ], were analyzed by univariate analysis ( Table 5 ). Barthel ≤ 40, HCA-urinary sepsis, and septic shock had statistically significant differences between the 30-day mortality group and the survivors in the univariate analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Known risk factors for 30-day mortality, such as age, comorbidity, dependency, HCA-urinary sepsis, septic shock and IEAT [ 31 , 32 , 33 , 34 , 35 ], were analyzed by univariate analysis ( Table 5 ). Barthel ≤ 40, HCA-urinary sepsis, and septic shock had statistically significant differences between the 30-day mortality group and the survivors in the univariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…IEAT was not related to mortality, as shown in another study with bloodstream infection [ 33 ] with 31.4% of patients with a UTI. However, it has been related to mortality in patients with UTI [ 31 , 34 ]. According to the results of this study, with patients admitted to a hospital ward with urinary sepsis, the clinical severity at admission (septic shock) is what determines the patient’s prognosis in the urinary sepsis [ 31 ], not the etiology due to MDRB or non-MDRB.…”
Section: Discussionmentioning
confidence: 99%
“…The sepsis mortality rate varies, commonly reported around 10%, depending on factors like sepsis source, population studied, local AMR prevalence, and management protocols [ 1 4 ]. However, our study found a lower mortality rate due to lower proportion of severe sepsis cases, a favourable Charlson score (0–1) in 60% of the cohort and timely management [ 16 , 17 ]. Still, severe sepsis cases had a notable 4.6% mortality rate.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings also indicate MDR pathogens as significant predictors of urosepsis mortality and organ failure. In a Swedish retrospective study community onset urosepsis with blood stream infection (2019 and 2020), low AMR rates were observed and inappropriate empirical treatment was associated with mortality [ 16 ]. In our study in 89% of cases, the pathogens were susceptible to the antibiotics given.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, stones block the ureter and cause hydronephrosis, which provides favorable conditions for the growth and reproduction of bacteria. (Holmbom, et al 2022) On the other hand, infection damages the urinary tract mucosa, upregulates osteopontin in renal tubular cells and changes the pH value of urine to promote the formation of urinary calculi. (Espinosa-Ortiz, et al 2019) To address this problem, removing stones as completely as possible has become the foundation of treatment.…”
Section: Introductionmentioning
confidence: 99%